CSF Leak After COVID‐19 Nasopharyngeal Swab: A Case Report. (20th February 2021) - Paquin, Rebecca; Ryan, Lindsey; Vale, Fernando L.; Rutkowski, Martin; Byrd, James Kenneth
Abstract : The nasopharyngeal swab has been used with increased frequency since the beginning of the COVID‐19 pandemic. Little has been written in the literature regarding the complications arising from this procedure, as it is generally accepted as safe. In this report, we describe a case in which a young woman sustained a traumatic skull base injury during a nasopharyngeal swab for COVID‐19. We then discuss the subsequent treatment and outcome. This case demonstrates the potential for significant complications arising from this widespread procedure and the necessity for awareness of these potential complications. Laryngoscope, 131:1927–1929, 2021